2013
DOI: 10.1136/bcr-2012-008182
|View full text |Cite
|
Sign up to set email alerts
|

Double migration of a schwannoma of thoracic spine

Abstract: SUMMARYMobile intraspinal tumours have rarely been reported. In most cases, mobile tumours such as schwannomas or ependymomas were located in the cauda equina. Perusal of the literature revealed only two reports of mobile schwannomas in the cervical and thoracic regions. We report a case of thoracic schwannoma which migrated twice in successive operations resulting in negative exploration in the expected area. The aim of this report is to remind the surgeons about the possibility of migration of intradural-ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…During operation, the tumor spontaneously extruded from the dural space with several strong CSF pulses. Therefore, changes in CSF dynamics due to blockage of CSF pathway by IDEM Lee DY and Chung HJ The Nerve 3(2) October 2017 73 Schwannoma mobility might result in failure to locate the tumor in initial operation, leading to unnecessary second operation [5][6][7]13) . Intraoperative myelography, ultrasonography, and MRI have been suggested as useful tools to locate mobile schwannomas 1,9,16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During operation, the tumor spontaneously extruded from the dural space with several strong CSF pulses. Therefore, changes in CSF dynamics due to blockage of CSF pathway by IDEM Lee DY and Chung HJ The Nerve 3(2) October 2017 73 Schwannoma mobility might result in failure to locate the tumor in initial operation, leading to unnecessary second operation [5][6][7]13) . Intraoperative myelography, ultrasonography, and MRI have been suggested as useful tools to locate mobile schwannomas 1,9,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Mobile intradural extramedullary (IDEM) schwannoma is a rare disease entity [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][17] . Only 24 cases of mobile schwannoma have been reported in the literatures [5][6][7]14,16) . The mobility of schwannoma might result in failure to locate the tumor during surgery 6,16) .…”
Section: Introductionmentioning
confidence: 99%
“…In cases of an intraoperative missing tumor, Tavy et al [13], Fujiwara et al [2] and Khan et al [6] performed resurgery, Hollin et al [3] applied laminectomy to T12 through L5, and Murai et al [18] performed laminectomy over an extended region. Friedman et al [1], Marin-Sababria et al [8], Kim et al [7], and Terada et al [14] recently reported that an additional laminectomy was required inevitably.…”
Section: Discussionmentioning
confidence: 99%
“…Kim, Namura y Khan et al [6][7][8] describen localizaciones cervicales y torácicas para un total de 6 pacientes. En estos casos publicados se presentaban síntomas, a menudo modificaciones en la cualidad del dolor, que fluctuaban en función de cambios posturales, hecho que se repite en el nuestro.…”
Section: Discussionunclassified